Aluminum tolerance in maize is associated with higher MATE1 gene copy number - Maron, Lyza G. (National Academy of Sciences, 2013)
Genome structure variation, including copy number variation and presence/absence variation, comprises a large extent of maize genetic diversity; however, its effect on phenotypes remains largely unexplored. Here, we describe how copy number variation underlies a rare allele that contributes to maize aluminum (Al) tolerance. Al toxicity is the primary limitation for crop production on acid soils, which make up 50% of the world’s potentially arable lands. In a recombinant inbred line mapping population, copy number variation of the Al tolerance gene multidrug and toxic compound extrusion 1 (MATE1) is the basis for the quantitative trait locus of largest effect on phenotypic variation. This expansion in MATE1 copy number is associated with higher MATE1 expression, which in turn results in superior Al tolerance. The three MATE1 copies are identical and are part of a tandem triplication. Only three maize inbred lines carrying the three-copy allele were identified from maize and teosinte diversity panels, indicating that copy number variation for MATE1 is a rare, and quite likely recent, event. These maize lines with higher MATE1 copy number are also Al-tolerant, have high MATE1 expression, and originate from regions of highly acidic soils. Our findings show a role for copy number variation in the adaptation of maize to acidic soils in the tropics and suggest that genome structural changes may be a rapid evolutionary response to new environments.